Study of Coal Drying Characteristics Using Boiler Blowdown in a Rotary Coal Dryer - Aripin Gandi Marbun; Bambang Arip Dwiyantoro; Alvin Mizrawan Tarmizi (JMES The International Journal of Mechanical Engineering and Sciences, 2022)
Drying lignite coal to reduce its moisture content has become popular in the last decade. Previously, coal dryers used typical energy such as steam, fuel, or electrical as heat sources. Waste energy had never been implemented in a coal dryer while using it would reduce the cost of production and raise the economic value of the coal itself. An experimental study of drying low-rank coal was conducted using waste energy boiler blowdown in a rotary coal dryer. With variations of 0.595 mm, 1.18 mm, and 4.75 mm coal particle size and the flow's changes of 20 kg/hour, 30 kg/hour, and 40 kg/hour. The hot air temperature of 70oC, mass flow rate of 36 kg/hour, and pressure of 0,03 MPa were the constant parameters on the 15 rpm rotary drum. The results found that the coal moisture decreased significantly at 0.595 mm particle size and 20 kg/hour of flow. The final coal moisture dropped by 20.685%, and the calorific value increased by 879.6 kcal/kg from its initial value. In addition, the efficiency of the rotary coal dryer is 81.8%.